In this case using the elimination method is actually easier, but the question asks you to use substitution method so....
2x+y= -10
3x-y=0
1st equation: It is better to isolate 2x on both sides because the y is going to be positive no matter what, 2x+y=-10 => y=-2x-10
If you isolated 3x for the 2nd equation, the y will be negative, and you have to divide the whole equation by -1 to make it positive
Now we got y=-2x-10, lets substitute it in the 2nd equation and solve for x:
3x-(-2x-10) = 0
5x+10=0
5x=-10
x=-2
Now lets solve for y:
3(-2)-y=0
-6-y=0
y=-6
Lets see if the same is applicable for 1st equation
2(-2)+(-6)=-10
-10=-10
Yess!!
(-2,-6) is the solution
The answer to the question is explained at the beginning
Hope it helps!